2013
DOI: 10.1111/jan.12180
|View full text |Cite
|
Sign up to set email alerts
|

Weaving dreamcatchers: mothering among American Indian women who were teen mothers

Abstract: Aims The aim of this study was to explore the mothering experience and practice among reservation based adult American Indian women who had been adolescent mothers. Background Adolescent American Indian women are at an elevated risk for teen pregnancy and poor maternal/child outcomes. Identifying mothering practices among this population may help guide intervention development that will improve health outcomes. Design A collaborative orientation to community based participatory research approach. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Analysis of both single and multiple responses to this question revealed that women admired their mothers the most but also looked up to their grandmothers, aunts, fathers, and older sisters. These findings reinforce a fundamentally Indigenous belief that childrearing is not restricted to the parents but, rather, is a role undertaken by the entire extended family [ 52 ]. Thus, these results support the recommendation that mother-daughter interventions also include extended family members who play a supportive role.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Analysis of both single and multiple responses to this question revealed that women admired their mothers the most but also looked up to their grandmothers, aunts, fathers, and older sisters. These findings reinforce a fundamentally Indigenous belief that childrearing is not restricted to the parents but, rather, is a role undertaken by the entire extended family [ 52 ]. Thus, these results support the recommendation that mother-daughter interventions also include extended family members who play a supportive role.…”
Section: Discussionsupporting
confidence: 74%
“…External validity is also limited due to the population-specific survey and the heterogeneity of AI tribes. With over 550 federally recognized tribes in the U.S., generalization of review findings to all AI tribes is not possible [ 52 ]. Findings are limited to the Diné and, potentially, other regional and/or matrilineal tribes.…”
Section: Discussionmentioning
confidence: 99%
“…Women demonstrated a desire to control their own bodies and maintain their own identities, especially when unexpected pregnancies disrupted their educational or career pursuits. Congruent with research done on teen pregnancies in NA tribes, whether children were planned or not, women's care for them shows that their children were wanted, claiming their power as mothers to keep their children in the face of historical and ongoing threats by authorities to determine their children's fate (Dalla & Gamble, 2001;Palacios et al, 2014). As Hill-Collins (1997) notes, "In such a situation, simply keeping and rearing one's children becomes empowerment" (p. 379).…”
Section: Discussionmentioning
confidence: 99%
“…including depression, mental distress, and cardiovascular health problems (Ciciolla & Luthar, 2019;Henderson et al, 2016;Manuel et al, 2012). However, relatively little research has explored the impact of these stressors for NA women (McKinley et al, 2019;Dalla & Gamble, 2001;Gurr, 2014;Palacios et al, 2014;Theobald, 2019) who are at much higher risk of postpartum depression (Baker et al, 2005), maternal morbidity and mortality (Gurr, 2014;Theobald, 2019), and death by suicide (Curtin & Hedegaard, 2019). These health implications underscore the importance of examining the responsibilities and expectations for contemporary NA mothers to inform social work practice with NA communities.…”
mentioning
confidence: 99%
“…All interviews were digitally recorded and later transcribed verbatim. Analysis comprised the triadic process (paradigm case, thematic analysis, and exemplars) described by Benner (1994) to obtain major themes that are presented in depth elsewhere (Palacios, Chesla, Kennedy, & Strickland, 2012; Palacios & Kennedy, 2010; Palacios, Strickland, Chesla, Kennedy, & Portillo, 2013).…”
Section: Case Study I: Storytelling and Listening As Data Collectionmentioning
confidence: 99%